Mythbusters in rowing medicine and physiotherapy: nine experts tackle five clinical conundrums - Wilson, F.; McGregor, A. (British Journal of Sports Medicine, 2014)
Any rower who presents with palpitations should be taken seriously, as these may be an indicator of significant cardiac arrhythmia. The many years of hard endurance training causes adaptive changes that are collectively known as the athlete's heart. Sometimes these changes progress from normal adaptation to volume overload to unhealthy sequelae. The most common arrhythmia seen in rowers is atrial fibrillation, and the longer the rower has been in heavy training, typically over 10 years, the more likely it is that they will develop this arrhythmia. The exact mechanism is unclear but it may be due to atrial enlargement with dilation and fibrosis plus a contribution from increased vagal tone and bradycardia. The condition presented dramatically for Rob Waddell in the trials for the single berth at Beijing Olympics. In New Zealand, several athletes rowing careers have been affected by atrial fibrillation or other arrhythmias. Nathan Cohen, gold medallist in the London 2012 Olympics, had to retire following several episodes of arrhythmia.